2002
DOI: 10.1046/j.0022-3042.2001.00748.x
|View full text |Cite
|
Sign up to set email alerts
|

The production of macrophage inflammatory protein‐2 induced by soluble intercellular adhesion molecule‐1 in mouse astrocytes is mediated by src tyrosine kinases and p42/44 mitogen‐activated protein kinase

Abstract: Severe traumatic brain injury stimulates the release of soluble intercellular adhesion molecule-1 (sICAM-1) into CSF. Studies in cultured mouse astrocytes suggest that sICAM-1 induces the production of macrophage inflammatory protein-2 (MIP-2). In the present study, we investigated the underlying mechanisms for MIP-2 induction. sICAM-1 induced MIP-2 in astrocytes lacking membrane-bound ICAM-1, indicating that its action is due to heterophilic binding to an undescribed receptor rather than homophilic binding to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 42 publications
0
40
0
Order By: Relevance
“…In static cell culture, sICAM-1 at physiologically relevant concentrations has been reported to induce expression of pro-inflammatory mediators (Otto, Heinzel-Pleines et al 2000;Otto, Gloor et al 2002). mRNA levels of IL-8 and MCP-1 were significantly increased 1hr after exposure to sICAM-1 in HUVECs ( figure 6A and B).…”
Section: Sicam-1 Contributes To Monocyte Recruitment By Endothelial Cmentioning
confidence: 82%
See 4 more Smart Citations
“…In static cell culture, sICAM-1 at physiologically relevant concentrations has been reported to induce expression of pro-inflammatory mediators (Otto, Heinzel-Pleines et al 2000;Otto, Gloor et al 2002). mRNA levels of IL-8 and MCP-1 were significantly increased 1hr after exposure to sICAM-1 in HUVECs ( figure 6A and B).…”
Section: Sicam-1 Contributes To Monocyte Recruitment By Endothelial Cmentioning
confidence: 82%
“…Two potential candidates for receptors have been suggested so far, namely the homophilic binding to membrane bound ICAM-1, or an unknown receptor of 49kD (Gho, Kleinman et al 1999;Otto, Gloor et al 2002). Otto et al showed that sICAM-1 did not bind to cell surface ICAM-1 using ICAM-1 deficient murine astrocytes but identified the involvement of an unidentified receptor (Otto, Gloor et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations